Simulation of microcrack growth and repair in living bone - Tisbo, Pietro (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2013)
As they are the structural components of the body, bones are subjected to the accumulation of damage because of cyclical stress (fatigue). The fatigue damage in bone takes the form of microscopic cracks (microcracks) that span the bone structure and with time can become a danger for the bone. Bones are able to repair damage by detecting the microcracks and using specialized cells that remove the old bone and replace it with new, undamaged bone. The goal of this work was to create a system able to simulate the mechanics of microcrack growth and repair in living bone knowing the properties of bone and the stress it is going to sustain.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin.